The governance of global value chains, the state, and small businesses: The case of timber in Myanmar - John Rand; Paula Castro Rodriguez; Finn Tarp; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
We use the case of the timber industry in Myanmar to analyse how national regulatory frameworks and international ecological discourses affect forest management and small businesses. The state plays two roles in the timber industry in Myanmar: it is the main producer and legal source of raw timber for the private sector; and it regulates timber extraction and the legality of operation of private sector firms. The state seeks a balance between forest conservation as a public policy objective and providing enough raw timber for the private sector. The implications of this for the private sector are twofold. The strict regulatory framework increases operational costs, as multiple licences and permits are required. And the state-controlled supply of raw materials results in inefficiencies, such as shortage and high raw timber prices. Under these conditions, the smallholder wood industry in Myanmar is at risk of stagnating at best, if not disappearing.
Keywords: Q23; Q28; L53; L23; 330; timber; wood; forestry; state; policy; Myanmar